Adverse Effect of Mixture of Food Additives on Some Biochemical Parameters in Male Albino Rats - Radwan, Eman Hashem; Mohamed Elghazaly, Mohamed; Hussein, Hussein Khamis; Abdel Aziz, Karolin Kamel; Barakat, Amel Ibrahim (JOURNAL OF ADVANCES IN BIOLOGY, 2020)
The present study investigated the unsafe impacts of sodium nitrite, sodium benzoate and their mixture which is utilized in fabricating of the food on some biochemical parameters in male albino rats. Rats (40) were divided into four groups as follows: group 1 used as the control, group II and III were treated orally with sodium nitrite nano2 (80 mg/kg BW) and sodium benzoate (SB) (200 mg/kg BW), respectively. Group IV was treated orally with a mixture of sodium nitrite and sodium benzoate. Rats took their respective doses every day for 8 weeks. The obtained results showed that sodium nitrite, sodium benzoate and their mixture (nano2 and SB) initiated a diminished within in the activity of antioxidant enzymes (SOD, CAT, and GSH) within the kidney, while, MDA recorded a highly significant activity level within experimental groups. Urea and creatinine mean levels were were expanded within plasma of the experimental rats. In the histology of the kidney, sections appeared edema with few mononuclear leukocyte cellular infiltrations, shrinkage of glomeruli. The severity of these changes increased in the experimental group which treated by the mixture of sodium nitrite and sodium benzoate. Overexpression in p53 occurred in experimental groups that were treated by nano2, SB and their mixture. The present study concluded that the mixture of food additives can induce toxicity in the kidney of rats. It is obvious that food additives induced nephrotoxicity within the kidney. It decreased the antioxidant enzymes (GSH, CAT, and SOD) and increased MDA. Increase tumor suppressor gene p53 in kidney tissue. Food added substances caused changes in biochemical parameters as in creatinine and urea. The utilization of food additives must be decreased. The presence of more than one type of food additives on our food and the usage of the mixture of sodium nitrite and sodium benzoate initiated changes in biochemical parameters and immune-histopathological changes.